Web-Based IT Helpdesk Ticketing System at PT. Dayacipta Kemasindo - Didi Kurnaedi; Erna Oktora; Eko Dharmawan; Irfan Nasrullah; Muhammad Drajat (Komunitas Dosen Indonesia, 2022)
An IT helpdesk is a software or system that helps users troubleshoot their IT facility through one or more points of contact. Then, it allows users to troubleshoot, track their problems, and get help with products or services. PT Dayacipta Kemasindo, in carrying out administrative processes, and work in the office, cannot be separated from the use of IT, so if there is a problem with IT facilities, it requires assistance from the IT department. However, there are several problems, one of which is that the department that reports disturbances and damage often does not know how long it will take for their issues to be handled because the process of queuing for work is not clearly visible, so it seems relatively slow. The purpose of this research is to develop an IT Helpdesk system for trouble reporting and monitoring repair work. The result of this research is a system that can be used by the IT department to help monitor incoming assignments and work.